Clinical Description, Molecular Analysis of TWIST2 Gene, and Surgical Treatment in a Patient With Barber-Say Syndrome. Issue 2 (March 2018) - Zuazo, Francisca; Astiazaran, Mirena C.; Rodríguez-Cabrera, Lourdes; Garcia-Regil, Patricia; Chacon-Camacho, Oscar; Tovilla-Canales, José L.; Zenteno, Juan C.
Abstract : Barber-Say syndrome is a rare autosomal dominant disease characterized by dysmorphic features, mainly of the eyelids and skin. It is caused by heterozygous mutations in gene TWIST2, localized in chromosome 2q37.3. The authors present the case of a pediatric patient with a clinical diagnosis of Barber-Say syndrome with ocular symptoms related to exposure keratitis. Molecular analysis of her DNA revealed a mutation on TWIST2 gene confirming the diagnosis of Barber-Say syndrome. Surgical treatment of the patient's eyelids resolved her signs and symptoms. Abstract : This is the first report of a Mexican patient with Barber-Say syndrome with molecular confirmation and a description of her eyelid surgery which had a favorable outcome.